Advanced glycation end products and glycosaminoglycans in patients with diabetic ketoacidosis. (March 2020) - Edriss, Hawa; Molehin, Adebayo James; Selvan, Kavitha; Gavidia, Rocio; Patel, Parth U; Nugent, Kenneth
In some patients diabetic ketoacidosis (DKA) causes acute endothelial injury and multiorgan failure. Measurement of glycosaminoglycan (GAG) and advanced glycation end products (AGE) could provide information to help understand the biochemical events associated with poor outcomes in these patients. This study included 37 patients with DKA admitted to an intensive care unit. Blood was collected from these patients during the first day of hospitalization, 24 hours after the first sample, and 72 hours after the first sample when possible. ELISA-based assays were used to measure glucose, hemoglobin A1c, AGE, glycated albumin, and GAG levels in serum. Twenty healthy control subjects with no history of diabetes donated 1 blood sample. Control subjects had a mean age of 36.3±12.1 years; patients with DKA had a mean age of 38.1±18.5 years. Admission laboratory tests in patients with DKA included glucose 546±296 mg/dL, bicarbonate 10.1±5.5 mEq/L, anion gap 31.8±7.8 mEq/L, and creatinine 1.1±1.0 mg/dL. Patients with DKA had significantly higher level glucose and free glycated hemoglobin. Control subjects had significantly higher levels of AGE and glycated albumin. There were no differences in soluble receptor for AGE levels or GAG levels between the control subjects and patients with DKA. Patients with DKA had lower circulating levels of AGE and glycated albumin than control subjects. These results may reflect absorption of these proteins to damaged capillary surfaces or loss of proteins into interstitial spaces secondary to increased endothelial permeability.